The Effect of Cooperative Learning Model Numbered Heads Together (NHT) Type on Student Learning Outcomes in Social Sciences Subjects in Grade V Elementary School - Resty Fauziah (Postgraduate School, Universitas Negeri Padang, 2019)
The purpose of this study was to examine the effect of the Numbered Heads Together (NHT) Cooperative Learning Model on Student Learning Outcomes in Social Sciences Subjects of Class V Elementary School. The study population was all fifth grade students of SD 21 Cindakir Bungus Bay, Kabung Bay, Padang City. The study sample was a fifth grade student at SD 21 Cindakir Bungus Bay, Kabung Bay, Padang City. Data from research results are obtained from student learning outcomes tests. The results of the study indicate that there is an influence of the Numbered Heads Together type Cooperative Learning Model on social studies learning outcomes in class V SD 21 Cindakir Bungus Bay, Kabung Bay, Padang City